Hubungan Dukungan Keluarga Dan Kepatuhan Diet Hipertensi Terhadap Tekanan Darah Pada Lansia - Meilinda Meilinda; Saka Adhijaya Pendit; Dayuningsih Dayuningsih (Universitas Muhammadiyah Manado, 2025)
The current increase in hypertension cases is closely related to changes in people's lifestyles, especially the habit of eating fast food and high-salt foods, potentially causing serious complications such as stroke and heart disease. Family support plays an important role in motivating and supervising the elderly to adhere to the recommended hypertension diet. The purpose of the study was to analyze Relationship between Family Support and Dietary Adherence Hypertension to Blood Pressure in the Elderly in Rw 07 Kebon Kosong Kemayoran 2024. The research design of this research design is cross sectional using a quantitative approach involving 65 elderly people as samples selected through purposive sampling and data collection techniques using questionnaire sheets. Data were analyzed using the chi-square test. The results showed that there was a relationship between family support and hypertension diet compliance with blood pressure in the elderly. with a p value (0.000), < p value (0.05). Based on the results of the study there is a relationship between family support and hypertension diet adherence to blood pressure in the elderly.